A review of the types of diets used in Crohn’s disease: the support system for pharmacological treatment - Śnieżna, Joanna; Wojciech Florczak, Wojciech; Dziewic, Jakub; Dzwonnik, Karol; Zelik, Urszula; Trestka, Gabriela; Domino, Wiktoria; Stępień, Kamila; Włodyka, Jagienka; Adamczyk, Sabina; et al. (Quality in Sport, 2025)
Crohn’s disease (CD) is a chronic and progressive disease, that requires a multilateral approach. Its incidence is rising globally, particularly in industrializing regions, correlating with increased consumption of ultra-processed foods. Besides pharmacological and surgical treatment, the diet component plays a crucial role in alleviating symptoms of the disease and preventing its progression. This review highlights the evolving role of dietary interventions as supportive treatments in CD management, complementing pharmacological and surgical approaches. This review represents the analysis of some of the most commonly used diets: the low FODMAP diet, Specific Carbohydrate Diet (SCD), Mediterranean diet, Crohn’s Disease Exclusion Diet (CDED), and exclusive enteral nutrition (EEN) in Crohn’s disease based on studies from PubMed’s articles published within the last five years. The aim of this systematic review is to highlight the importance of dietary element in the management of CD and a wide range of new methods of supporting treatment. Dietary interventions provide significant potential to modulate inflammation, support remission, and improve the quality of life in CD patients. Further research in personalized dietary protocols will help incorporate into multidisciplinary approaches for the treatment.